20.6k views
2 votes
X | 9 | -11 | 7 | 11 | -6 | -13

f(x) | 11 | 4 | -6 | -1 | -15 | -5
Find the following values:
f^-1 (-15) =
f^-1 (4) + f(9)

User Skytunnel
by
6.7k points

1 Answer

4 votes

Final answer:

To find f^-1(-15), we find the input value that corresponds to the output of -15. To find f^-1(4) + f(9), we find the input value corresponding to 4, add it to the value of f(9).

Step-by-step explanation:

To find the value of f-1(-15), we need to find the input value that corresponds to the output of -15. From the table, we can see that when x = -13, f(x) = -15. Therefore, f-1(-15) = -13.

To find the value of f-1(4) + f(9), we first find f-1(4), which corresponds to an input value of x = 7 from the table. Then we find f(9), which equals 11. Adding these values together, we get f-1(4) + f(9) = 7 + 11 = 18.

User Iizno
by
7.0k points